2012
DOI: 10.1007/s11250-012-0337-4
|View full text |Cite
|
Sign up to set email alerts
|

Mineral deficiency status of ranging zebu (Bos indicus) cattle around the Gilgel Gibe catchment, Ethiopia

Abstract: Mineral deficiencies in cattle, widespread in East Africa, impair optimal health and production and consequently place a great burden on the farmers' income. Therefore, detection of shortages and imbalances of specific minerals is essential. Our objective was to evaluate the mineral status of grazing cattle around the Gilgel Gibe catchment in Ethiopia and associated factors. In study I, individual animal plasma and herd faecal Ca, P, Mg, Na, K, S, Fe, Zn, Mn and Cu concentrations were determined in adult zebu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 17 publications
1
16
1
Order By: Relevance
“…The evolution of plasma Fe concentration over time did not differ between the 2 breed types of cattle. However, zebu cattle did have more variable and greater liver Fe concentrations than crossbred cattle, which were also greater than found in previous research in the area (Dermauw et al, 2013a). Although this difference seems to contradict the ceruloplasmin explanation of Hansen et al (2010), dietary Cu levels were lower than in the supplemented study group of Hansen et al (2010), and therefore, the range in Cu status is much smaller in our study.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…The evolution of plasma Fe concentration over time did not differ between the 2 breed types of cattle. However, zebu cattle did have more variable and greater liver Fe concentrations than crossbred cattle, which were also greater than found in previous research in the area (Dermauw et al, 2013a). Although this difference seems to contradict the ceruloplasmin explanation of Hansen et al (2010), dietary Cu levels were lower than in the supplemented study group of Hansen et al (2010), and therefore, the range in Cu status is much smaller in our study.…”
Section: Discussioncontrasting
confidence: 84%
“…Mineral imbalances in the soil and consequently in the plants growing on this soil often aggravate this situation (Haque et al, 1993). In Ethiopia, copper deficiency is a frequent problem when grazing on pastures, as low levels of Cu are accompanied by high levels of Mo and S and very high levels of Fe (Roeder, 1980;Faye and Grillet, 1984;Faye et al, 1991;Dermauw et al, 2013a). Consequently, deficiencies of Cu are to be expected in cattle in these regions.…”
Section: Introductionmentioning
confidence: 99%
“…Concomitantly with the low dietary trace element supply found in the Gilgel Gibe catchment, low trace element concentrations were found in transport and storage pools of sampled zebu-influenced cattle in the region (Dermauw et al, 2013a(Dermauw et al, , 2014a. More specifically, Cu deficiency was observed in almost half of the sampled animals, based on status evaluation by means of plasma and liver samples (Figure 2).…”
Section: Results and Conclusionmentioning
confidence: 88%
“…In two studies, individual plasma and pooled herd faeces were sampled in adult zebu cattle grazing at the catchment (n = 90) and liver in adult zebu bulls slaughtered at the local abattoir (n = 53) (Dermauw et al, 2013a) and trace element concentrations in these samples were determined. Meanwhile, the impact of sex, age, body condition and the presence of parasitic infections was analysed.…”
Section: Figure 1 Zebu Oxes Ploughing the Land At The Gilgel Gibe Camentioning
confidence: 99%
“…Furthermore, it found that iron is an important component of red blood cells that plays an essential role in haematopoiesis. The use of iron supplementation from wallaby bones may prevent iron deficiency anaemia [24]. …”
Section: Resultsmentioning
confidence: 99%